2020
DOI: 10.21037/jgo-20-220
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant therapy in locally advanced colon cancer: a meta-analysis and systematic review

Abstract: Background: The role of perioperative or neoadjuvant chemotherapy for locally advanced colon cancer is unclear. Emerging evidence such as the FOXTROT trial is challenging the conventional norm of upfront operation for these patients. However, these trials have yet to reach statistical significance. Methods: MEDLINE, Embase, Cochrane Library, China Knowledge Resource Integrated Database (CNKI) and ClinicalTrials.gov were searched. Randomized controlled trials (RCTs) and observational studies of patients with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 47 publications
5
45
0
1
Order By: Relevance
“…For non-hematologic AEs, the incidence of severe AEs was <10%. This result was consistent with our previous studies [ 6 , 11 , 19 , 48 ], and we suggested that neoadjuvant CCRT is a safe and tolerable treatment for patients with LACC.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…For non-hematologic AEs, the incidence of severe AEs was <10%. This result was consistent with our previous studies [ 6 , 11 , 19 , 48 ], and we suggested that neoadjuvant CCRT is a safe and tolerable treatment for patients with LACC.…”
Section: Discussionsupporting
confidence: 93%
“…Obviously, an accurate CT scan image is essential in our treatment program. Many articles have described that CT is a reliable examination to assess the colon cancer stage and devise the subsequent surgical plan [ 7 , 11 , 12 , 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possible benefit is the option of neoadjuvant chemotherapy, which has recently been shown to improve oncological outcomes in locally advanced colon cancer [25, 26]. Neoadjuvant chemotherapy can result in downstaging and tumour regression in patients with obstructing or high risk colon cancer [27–30]. In the present study, 24% of the patients with right‐sided colon cancer and 29% of the patients with left‐sided colon cancer that were diverted received neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 79%